Typological features of skeletal muskles' power support and work capacity of speed skiers - Bogatov, A. A. (Teorija i Praktika fiziceskoj Kul'tury, 2001)
The purpose of this research was the study the typological features of speed skiers' skeletal muscles' energetics and their interrelation with the working capacity during a year training cycle. The results of the research specify the importance of giving attention to typological features of human's skeletal muscles when selecting them for sports schools and when programming their training process.